THE EFFECTIVENESS OF METACOGNITIVE INSTRUCTION TO TEACH LISTENING SKILL VIEWED FROM STUDENTS’ SCHEMATA - Hamid Asman (IKIP PGRI Pontianak, 2015)
The objectives of this research are to reveal whether: (1) Metacognitive instruction method is more effective than Cognitive instruction method to teach listening skill; (2) the students with high level of schemata have better listening skill than those with low level of schemata; and (3) there is an interaction between the teaching methods and students’ schemata in teaching listening skill. This experimental study was carried out at the English Education Department of IKIP-PGRI Pontianak in the Academic Year of 2014/2015. Data analysis reveals research findings as follows: (1) Metacognitive Instruction Method is significantly different from Cognitive instruction method to teach listening skill; (2) The listening skill of the students who have high schemata is significantly different from that of those who have low schemata; and (3) There is an interaction between teaching methods and students’ schemata for teaching listening skill. Based on the findings, it can be concluded that Metacognitive Instruction Method is effective to teach listening skill. The effectiveness of the method depends on the degree of the students’ schemata. Key word : Metacognitive Instruction,Ccognitive Instruction, Listening Skill, Students’ Schemata and Experimental Study.